Field Response of Magnetic Vortices in Dusty Olivine From the Semarkona Chondrite. (18th March 2019) - Nichols, Claire I. O.; Einsle, Joshua F.; Im, Mi‐Young; Kasama, Takeshi; Saghi, Zineb; Midgley, Paul A.; Harrison, Richard J.
Abstract: Recent paleomagnetic studies have constrained the strength and longevity of the magnetic field generated by the solar nebula, which has broad implications for the early evolution of the solar system. Paleomagnetic evidence was recorded by nanoscale iron inclusions in olivine crystals in the Semarkona LL 3.0 chondrite. These dusty olivines have been shown to be credible carriers of ancient magnetic remanence. The small scale of the iron inclusions presents several challenges for defining their fundamental magnetic properties. Here we present the first correlative study of the response of these magnetic structures under applied laboratory fields. Results show that the majority of particles are in a single‐vortex state and exhibit stable magnetic behavior in applied fields up to 200 mT. Experimental observations using Lorentz microscopy and magnetic transmission X‐ray microscopy are shown to compare well with the results of finite‐element micromagnetic simulations derived from 3‐D models of the particles obtained using electron tomography. This correlative approach may be used to characterize the fundamental magnetic behavior of many terrestrial and extraterrestrial paleomagnetic carriers in the single‐vortex to multivortex size range, which represent the vast majority of stable magnetic carriers in rocks and meteorites. Plain Language Summary: Some of the first solid materials to form in the solar system have been brought to Earth by meteorites. They contain tiny metallic inclusions that record information about the magnetic fields at the earliest stages of our solar system's history. Understanding these magnetic fields, and how they are recorded by metallic particles, provides very important information for understanding how our solar system formed and evolved. We have studied some of these particles to image their magnetic structure using microscopes, which allow us to see structures a billionth of a meter in size. We have developed a new technique using X‐rays to image how the magnetic structure in these particles changes when we apply different magnetic fields in the laboratory. We have also been able to reproduce our results using computer simulations of the magnetic behavior of the particles. This is the first study that has imaged the magnetic structure of these particles under applied fields. We find that the particles are very stable; even under magnetic fields thousands of times stronger than Earth's, the particles still do not change the magnetic structure they had in the early solar system. Key Points: We show the first experimental results demonstrating the stability of dusty olivines under applied magnetic fields We use a novel combination of electron and X‐ray microscopy techniques combined with micromagnetic simulations We confirm previous results that dusty olivines are capable of recording magnetic fields from the solar nebula